Histone turnover and chromatin accessibility: Critical mediators of neurological development, plasticity, and disease. (15th March 2016) - Wenderski, Wendy; Maze, Ian
Abstract : In postmitotic neurons, nucleosomal turnover was long considered to be a static process that is inconsequential to transcription. However, our recent studies in human and rodent brain indicate that replication‐independent (RI) nucleosomal turnover, which requires the histone variant H3.3, is dynamic throughout life and is necessary for activity‐dependent gene expression, synaptic connectivity, and cognition. H3.3 turnover also facilitates cellular lineage specification and plays a role in suppressing the expression of heterochromatic repetitive elements, including mutagenic transposable sequences, in mouse embryonic stem cells. In this essay, we review mechanisms and functions for RI nucleosomal turnover in brain and present the hypothesis that defects in histone dynamics may represent a common mechanism underlying neurological aging and disease. Abstract : Wenderski and Maze discuss an emerging role for replication‐independent (RI) nucleosomal dynamics/chromatin accessibility in orchestrating cell type‐specific transcriptional responses in brain, synaptic plasticity, and cognition. The authors review and hypothesize on the mechanisms involved in this process and provide evidence for a relationship between defects in RI histone turnover and neurological disease.